Representasi Gender dan Ekologi di Media: Perspektif Ekofeminis: Representation of Gender and Ecology on Media : an Ecofeminist Perspective - Ngatma’in, Ngatma’in; Budiman, Agus; Firdaus, Akhlis Nastainul; Roisiah, Riska Rahayu (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Critical views see the media not only as a tool of the dominant group but also as a producer of ideology. The media helps spread its ideas and control other groups, it is also a subject that constructs reality, complete with its views, biases, and partisanship. Suara Aisyiyah magazine is one of the mass media published since 1926 and is the oldest women's magazine in Indonesia. So it is very interesting to read how Suara Aisyiyah provides discourse on ecofeminism. An approach that seeks to understand and address the root causes of social injustice, ecological imbalance, and exploitation of nature by linking the close relationship between the oppression of women and the oppression of nature. This study uses a qualitative descriptive analysis research method by describing each data which is then analyzed in detail and synthesized effectively. The results state that Ecofeminism in the Suara Aisyiyah magazine that is built is a relationship related to the role of women in nature conservation in the form of protection, utilization, and preservation of natural resources, maintaining family food security, and access to utilizing natural resources for the daily economy.